Vitamin D3-associated lyotropic liquid crystalline nanoparticles for gemcitabine and thymoquinone delivery for treatment of luminal breast cancer with resistant characteristics - Loo, Yan Shan (2023)
Breast cancer is a leading cause of cancer death in women worldwide. About 70 – 80% of breast cancers are estrogen receptor-alpha (ERα) positive, dependent on estrogen for growth. Primary or acquired resistance towards endocrine therapy has remained a therapeutic barrier for patients in this subgroup, hence, there is an increasing interest in the development of novel targeted anticancer treatment strategies, including cancer nanomedicines that potentially translate to enhanced efficacy and reduced toxicity. Lyotropic liquid crystalline nanoparticles (LLCNs) are formed via self-assembly of amphiphilic molecules in a mixture composed of a lipid-based fraction, stabilizer and/or surfactant, and aqueous media/dispersant. The unique tunable modality of LLCNs presents the development of versatile nanostructures for a range of biomedical application. In this study, multifunctional LLCNs were investigated for gemcitabine-thymoquinone (Gem-TQ) co-delivery and targeting to hormone receptor-positive (HR+) breast cancer cells with potential resistance against tamoxifen (i.e., TamR cells) by surface modification with vitamin D3-polyethylene glycol (VD-PEG). LLCNs were prepared using soy phosphatidylcholine (SPC), phytantriol (PHYT), or glycerol monostearate (MYVR), in optimized ratios containing citrem or Poloxamer 407 (F127). The series of nanoformulation exhibited hydrodynamic particle sizes ranging between 96 – 365 nm, lattice parameters between 4.8 – 8.0, negative zeta potential between -4 to -79 mV, hexagonal, cubic, or micellar phases, and high entrapment efficiency. Low cytotoxicity of SPC/citrem LLCNs was demonstrated in non-malignant breast epithelial MCF10A cells consistent with modulation of hemocompatibility. Therefore, SPC/citrem was selected for co-encapsulation, whereby entrapment efficiency of 99.5 ± 0.1% (TQ) and 98.3 ± 0.1% (Gem) was demonstrated by SPC/citrem/Gem-TQ LLCNs comprising an optimized composition of 2.5:2.5 wt% of SPC:citrem, and 2:9 μM ratio of Gem and TQ. Meanwhile, the formulation with the addition of VD-PEG was designated as VD/SPC/citrem/Gem-TQ and the entrapment efficiency was 99.0 ± 0.1% (TQ) and 97.7 ± 0.1% (Gem) at the compositional ratio of 2.5:2.5:0.1 wt% of SPC: citrem:VD-PEG. Notably, the inhibitory concentrations (IC50s) following 24 h treatment with drug-loaded SPC/citrem/Gem-TQ were 14.5 ± 3.0 μM and 19.6 ± 2.3 μM, while IC50s of VD/SPC/citrem/Gem-TQ nanodispersion were 33.4 ± 8.0 μM and 9.7 ± 1.1 μM against MCF7 and T-47D-TamR breast cancer cells, respectively. Synergistic interaction between Gem and TQ shown in MCF7 cells was retained by SPC/citrem/Gem-TQ (i.e., treatment time of 24 h and fractional inhibition of 0.5), and by VD/SPC/citrem/Gem-TQ (i.e., treatment time of 24 h and fractional inhibition of 0.95), against T-47D-TamR cells. In addition, VD/ SPC/citrem/Gem-TQ LLCNs upregulated the expression of caspase-3, Akt-1 (serine/threonine-protein kinase) and vitamin D3-receptor (VDR) in T-47D-TamR cells, and cell cycle arrest at G2 phase (15.25% of total cell population) was evident following the treatment with VD/SPC/citrem/Gem-TQ LLCNs. Herein, multifunctional biocompatible LLCNs were described as a potential therapeutic co-delivery system for luminal breast cancer treatment.